Culture ,Self and Other Relation (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
In the wake of the significant advancements at all levels associated with  the crisis  and  different shifts ,most importantly the technology triumph against morals ,values ,customs and the ancient intellects drives into a  gab escalation among generations due to the diversity at the levels of the intellects ,manufactures and also the social and cultural structures. Thus, it must be searching for a new and different culture adequate to the nature of the new era with its enormous shifts at political ,industrial ,social and intellectual sectors ,which assign a new and different approach of communicating the intellects which  differently are being in a new place and time carried out the characteristics of the new culture. However ,it aims to shrink the distances among the far -away generations and attains a cultural form associates the backward -societies which , targets advancement like the West.